Faces of Politicians: Babyfacedness Predicts Inferred Competence but Not Electoral Success - Panu Poutvaara; Henrik Jordahl; Niclas Berggren (Research Institute of Industrial Economics (IFN), 2009)
Recent research has documented that competent-looking political candidates do better in U.S. elections and that babyfaced individuals are generally perceived to be less competent than maturefaced individuals. Taken together, this suggests that babyfaced political candidates are perceived as less competent and therefore fare worse in elections. We test this hypothesis, making use of photograph-based judgments by 2,772 respondents of the facial appearance of 1,785 Finnish political candidates. Our results confirm that babyfacedness is negatively related to inferred competence in politics. Despite this, babyfacedness is either unrelated or positively related to electoral success, depending on the sample of candidates.
Keywords: D72; J45; J70; 330; Babyfacedness; Competence; Beauty; Trustworthiness; Elections; Politiker; Qualifikation; Vertrauen; Wahlverhalten; Finnland